Stress sensing in plants by an ER stress sensor/transducer, bZIP28 - Srivastava, Renu; Deng, Yan; Howell, Stephen H. (Frontiers in Plant Science, 2014)
Two classes of ER stress sensors are known in plants, membrane associated bZIP transcription factors and RNA splicing factors. ER stress occurs under adverse environmental conditions and results from the accumulation of misfolded or unfolded proteins in the ER lumen. One of the membrane-associated transcription factors activated by heat and ER stress agents is bZIP28. In its inactive form, bZIP28 is a type II protein with a single pass transmembrane domain, residing in the ER. bZIP28’s N-terminus, containing a transcriptional activation domain, is oriented towards the cytoplasm and its C-terminal tail is inserted into the ER lumen. In response to stress, bZIP28 exits the ER and moves to the Golgi where it is proteolytically processed, liberating its cytosolic component which relocates to the nucleus to upregulate stress-response genes. bZIP28 is thought to sense stress through its interaction with the major ER chaperone, BIP. BiP binds to bZIP28’s lumenal domain under unstressed conditions and retains it in the ER. BIP binds to the intrinsically disordered regions on bZIP28’s lumen-facing tail. A truncated form of bZIP28, without its C-terminal tail is not retained in the ER but migrates constitutively to the nucleus. Upon stress, BiP releases bZIP28 allowing it to exit the ER. One model to account for the release of bZIP28 by BiP is that BiP is competed away from bZIP28 by the accumulation of misfolded proteins in the ER. However, other forces such as changes in energy charge levels, redox conditions or interaction with DNAJ proteins may also promote release of bZIP28 from BiP. Movement of bZIP28 from the ER to the Golgi is assisted by the interaction of elements of the COPII machinery with the cytoplasmic domain of bZIP28. Thus, the mobilization of bZIP28 in response to stress involves the dissociation of factors that retain it in the ER and the association of factors that mediate its further organelle-to-organelle movement.